PERAN SELF-ESTEEM DALAM MENCEGAH EMOTIONAL DISTRESS: LOCUS OF CONTROL SEBAGAI ANTECEDENT - Lukas Juliano; P. Tommy Y.S. Suyasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Nowadays, there are several phenomenons of suicide in-between university students whom are doing their thesis in Indonesia. One of the sources of suicide is emotional distress. Emotional distress is an uncomfortable state which can cause several lose, usually marked by depression and/or anxiety symptoms. There exist a few anti-stress variables to help coping process toward emotional distress, two of which are self-esteem and locus of control. This experiment’s goal is to figure out the state of the three variables on university students currently doing their thesis, while figuring out the relations of the anti-stress variables to emotional distress in the process of doing so. The participants in this experiment is 163 university students from X University currently doing their thesis, with age between 20-24 years old. From the data analysis, there are two conclusions. First, emotional distress is higher in university student doing thesis than common individual. Second, emotional distress can be predicted by self-esteem; furthermore, self-esteem is predicted by locus of control. The experiment is hoped to be able to provide insight in preventing emotional distress, specifically in university student struggling with their thesis. Saat ini, terdapat beberapa fenomena bunuh diri di kalangan mahasiswa yang sedang mengerjakan skripsi di Indonesia. Salah satu penyebab naiknya tingkat bunuh diri adalah emotional distress. Emotional distress adalah keadaan tidak menyenangkan yang dapat mengakibatkan berbagai kerugian, umumnya ditandai dengan gejala depresi dan/atau kecemasan. Terdapat beberapa variabel anti-stres yang terbukti mampu mengurangi emotional distress, dua di antaranya adalah self-esteem dan locus of control. Penelitian ini bertujuan memeroleh gambaran ketiga variabel ini pada mahasiswa yang sedang mengerjakan skripsi, sekaligus mencari peran kedua variabel anti-stres tersebut terhadap emotional distress pada partisipan penelitian. Partisipan penelitian meliputi 163 orang mahasiswa yang sedang menyusun skripsi, dengan rentang usia 20 hingga 24 tahun. Berdasarkan analisis data, diperoleh dua kesimpulan. Pertama, tingkat emotional distress pada mahasiswa yang sedang mengerjakan skripsi, lebih tinggi dibandingkan individu pada umumnya. Kedua, emotional distress dapat diprediksi oleh self-esteem; dan lebih lanjut self-esteem diprediksi oleh locus of control. Penelitian ini bermanfaat memberikan insight dalam pencegahan emotional distress, khususnya pada mahasiswa yang sedang mengerjakan skripsi.